2012
DOI: 10.4236/jep.2012.33035
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Humic Substances from Highly Humic Volcanic Ash Soil as Affected by Anionic Surfactant, Electrolyte Concentration and pH

Abstract: Dissolved humic substances separated from soils play an important role in the material cycle because they adsorb nu-trients and contaminants and move with water. This study was conducted to investigate the influence of anionic surfac-tant, pH and electrolyte concentration on the dissolution of humic substances from a highly humic volcanic ash soil. The soil used in the experiment has a negative charge and the anionic surfactant, sodium dodecylbenzene sulfonate, has also the negative charge. The absorbance of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A reduction in DS concentration was observed when using the 100 mmol NaCl/L solution as an extractant (Figures 1 and 2). This was caused by the shielding effect exerted by the higher electrolyte concentration, which weakened the repulsive electrostatic forces among the negatively charged aggregated organic matters in the soil, making it difficult for the DS to dissolve into the solution (Ahmed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in DS concentration was observed when using the 100 mmol NaCl/L solution as an extractant (Figures 1 and 2). This was caused by the shielding effect exerted by the higher electrolyte concentration, which weakened the repulsive electrostatic forces among the negatively charged aggregated organic matters in the soil, making it difficult for the DS to dissolve into the solution (Ahmed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that the high turbidity of the soil solution is caused by the presence of the DOM, especially when humic substances are present at considerably higher quantities. The DOM concentration increased with higher pH, lower electrolyte concentration and higher anionic surfactant concentration when a highly humic soil was shaken with the solution (Ahmed, Ishiguro, & Akae, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates cooperative adsorption, which is generated by the lateral attraction among the hydrophobic tails of SDS. The decrease of anionic surfactant adsorption with the increase of pH and/or the decrease of the electrolyte concentration and the cooperative adsorption at lower surfactant concentration was also observed for highly humic soil by Ahmed et al (2012a) and Ahmed and Ishiguro (2015). However, the adsorption amount was much larger because the highly humic soil has much amount of hydrophobic surface.…”
Section: Discussionmentioning
confidence: 74%
“…It has been observed that DBS adsorption decreased as pH increased (Inoue et al 1978;Fytianos et al 1998;Li et al 2008;Ahmed et al 2012b) and that DBS adsorption correlated positively with organic matter content (McAvoy et al 1994;Fytianos et al 1998). The effect of pH and DBS concentration on the dissolution of humic substances from highly humic volcanic ash soil at different electrolyte concentrations has also been observed (Ahmed et al 2012a). Koopal et al (1995) have studied the influence of electrolyte concentration on the adsorption of ionic surfactants onto oppositely charged metal oxide surfaces.…”
Section: Introductionmentioning
confidence: 98%